2018
DOI: 10.1016/j.isci.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Plasticity Scales Dendritic Spine Volumes and Changes the Threshold and Specificity of Hebbian Plasticity

Abstract: SummaryInformation is encoded in neural networks through changes in synaptic weights. Synaptic learning rules involve a combination of rapid Hebbian plasticity and slower homeostatic synaptic plasticity that regulates neuronal activity through global synaptic scaling. Hebbian and homeostatic plasticity have been extensively investigated, whereas much less is known about their interaction. Here we investigated structural and functional consequences of homeostatic plasticity at dendritic spines of mouse hippocam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 56 publications
7
30
2
2
Order By: Relevance
“…39,40 Several forms of homeostatic plasticity have been identified and include mechanisms that regulate neuronal excitability, stabilize total synaptic strength, and influence the rate and extent of synapse formation. 41 These forms of homeostatic plasticity are likely to complement Hebbian mechanisms to allow the modification of neuronal networks selectively. 41 In essence, the whole synaptic population is equally affected, such that the overall sum of synaptic strengthening and therefore activity of a neuron is changed but the relative weighed differences between synapses is preserved: the computational and storage capacity of the network is not compromised and homeostatic plasticity will not be in conflict with or erase the information set by Hebbian plasticity.…”
Section: Synaptic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Several forms of homeostatic plasticity have been identified and include mechanisms that regulate neuronal excitability, stabilize total synaptic strength, and influence the rate and extent of synapse formation. 41 These forms of homeostatic plasticity are likely to complement Hebbian mechanisms to allow the modification of neuronal networks selectively. 41 In essence, the whole synaptic population is equally affected, such that the overall sum of synaptic strengthening and therefore activity of a neuron is changed but the relative weighed differences between synapses is preserved: the computational and storage capacity of the network is not compromised and homeostatic plasticity will not be in conflict with or erase the information set by Hebbian plasticity.…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…41 These forms of homeostatic plasticity are likely to complement Hebbian mechanisms to allow the modification of neuronal networks selectively. 41 In essence, the whole synaptic population is equally affected, such that the overall sum of synaptic strengthening and therefore activity of a neuron is changed but the relative weighed differences between synapses is preserved: the computational and storage capacity of the network is not compromised and homeostatic plasticity will not be in conflict with or erase the information set by Hebbian plasticity. 41 The Aged Glutamatergic Synapse According to the World Health Organization (WHO), by 2020, the number of people aged 60 years and older will outnumber children younger than 5 years.…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…To ensure that no significant biological remodeling occurred either at the dendrite or spines over the course of the in-vitro experiment we acutely added tetrodotoxin (TTX) into the artificial cerebrospinal fluid (ACSF) used to perfuse the neuron during the imaging session. It has been shown that application of TTX changes spine volumes only upon prolonged application 40 . We subsequently analyzed spines to investigate if the segmentation performance and resulting IFI volumes were sensitive to different levels of fluorescence.…”
Section: Fluorescence Intensity Invariant Performance In Spine Segmenmentioning
confidence: 99%
“…This form of plasticity is inherently unstable, as a small change in synaptic strength can promote further change in the same direction, and this positive reinforcement can drive synaptic efficacies to either saturate or reduce to a minimum (Abbott & Nelson, ; Honnuraiah & Narayanan, ; Hobbiss et al . ). It has long been recognized that Hebbian rules need to be supplemented with additional stabilizing mechanisms to curb runaway plasticity and support stable yet flexible neural circuits (Abbott & Nelson, ; Zenke & Gerstner, ; Keck et al .…”
Section: Introductionmentioning
confidence: 97%